EFEKTIFITAS PENGGUNAAN APLIKASI QUIZIZZ TERHADAP MINAT DAN HASIL BELAJAR MATEMATIKA SISWA - Aprilla Putri; Machrani Adi Putri Siregar (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This research aims to determine the effectiveness of using the Quizizz application on students' interest and learning outcomes in mathematics on exponents and root forms at Muhammadiyah 48 Medan Private Middle School. The background to this research focuses on the low interest and learning outcomes of students in mathematics subjects, which are often considered difficult and boring by many students. The method used is quantitative with a pre-experimental research design, namely one group pretest posttest design where the sample consists of 50 students selected using total sampling techniques. The results of the research show that there is a significant increase in student interest and learning outcomes after using the Quizizz application, namely scores The average interest in learning mathematics after using the Quizizz application is 76.54 with a gain value in the medium category of 0.448 and the average score for learning mathematics after using the Quizzizz application is 78.60 with a gain value in the medium category 0.478. The paired sample t-test produced a significance value of less than 0.05, namely 0.001, indicating that the use of the Quizizz application was effective in increasing students' interest and learning outcomes in mathematics. So it can be concluded that the integration of technology in learning, especially through the Quizizz application, has been proven to be able to make mathematics learning more interesting, fun and interactive, thereby increasing students' interest and learning outcomes in mathematics.